2022
DOI: 10.3390/rs14133238
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Forest Loss and Gain Patterns in Subtropical China Detected Using an Integrated LandTrendr and Machine-Learning Method

Abstract: China has implemented a series of forestry law, policies, regulations, and afforestation projects since the 1970s. However, their impacts on the spatial and temporal patterns of forests have not been fully assessed yet. The lack of an accurate, high-resolution, and long-term forest disturbance and recovery dataset has impeded this assessment. Here we improved the forest loss and gain detections by integrating the LandTrendr change detection algorithm with the Random Forest (RF) machine-learning method and appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 61 publications
3
9
0
Order By: Relevance
“…Xian et al [61] showed that forest change losses in Guangdong Province between 1980 and 2015 were mainly influenced by economically oriented factors, although deforestation driven by economic factors was limited by forest management policies. In addition, the "Guidance on Strengthening the Management of Collective Forest Resources and Prohibiting Indiscriminate Logging in the South" was promulgated in 1987 to curb the uncontrolled logging resulting from the "three determinations" policy; however, forest disturbance in Guangdong Province has remained high over recent decades [38]. Since mature and overmature forests are almost completely logged, consequently, the remaining disturbed forests also tend to be younger.…”
Section: Methodology For Forest Age Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…Xian et al [61] showed that forest change losses in Guangdong Province between 1980 and 2015 were mainly influenced by economically oriented factors, although deforestation driven by economic factors was limited by forest management policies. In addition, the "Guidance on Strengthening the Management of Collective Forest Resources and Prohibiting Indiscriminate Logging in the South" was promulgated in 1987 to curb the uncontrolled logging resulting from the "three determinations" policy; however, forest disturbance in Guangdong Province has remained high over recent decades [38]. Since mature and overmature forests are almost completely logged, consequently, the remaining disturbed forests also tend to be younger.…”
Section: Methodology For Forest Age Estimationmentioning
confidence: 99%
“…Subsequently, we calculated the annual maximum of the time series of normalized burn ratio (NBR) based on Landsat data, which served as input for the LandTrendr algorithm. NBR is highly sensitive to forest disturbance and restoration [38,51,52], with higher NBR values typically indicating healthy and dense vegetation, and can be calculated using Equation (1).…”
Section: Landsat Imagerymentioning
confidence: 99%
See 1 more Smart Citation
“…There are several possibilities for this to happen. Another effect is a bad image due to the influence of clouds at the research location [Shen et al, 2022] or no significant changes within a certain period.…”
Section: Vegetation Changementioning
confidence: 99%
“…The dynamic change of vegetation can be monitored by observing the spectral trajectory of an individual pixel over time (Yang et al, 2018). Taking advantage of prolonged Landsat data acquisition, Kennedy et (Shen et al, 2022;Yin et al, 2022). This study aimed to identify the trends of forest change using the LandTrendr approach, taking a case study in a social forestry area in Pati, Indonesia.…”
Section: Introductionmentioning
confidence: 99%